Phacoemulsification plus endoscopic cyclophotocoagulation versus phacoemulsification alone in primary open-angle glaucoma. Issue 2 (March 2018) - Pérez Bartolomé, Francisco; Rodrigues, Ian A.; Goyal, Saurabh; Bloch, Edward; Lim, Wei S.; Alaghband, Pouya; Guajardo, Jose; Jones, Stephanie; Lim, Kin S.
Purpose: To examine the efficacy and safety of combined phacoemulsification and endoscopic cyclophotocoagulation (phaco-ECP) compared to phacoemulsification alone in patients with primary open-angle glaucoma (POAG). Methods: We performed a retrospective notes review of 99 consecutive clinical records of patients with POAG from 2 London eye departments. A total of 69 patients who underwent phaco-ECP and 30 sex- and age-matched control patients who underwent cataract surgery alone were included. Data on intraocular pressure (IOP), visual acuity (VA), number of ocular hypotensive medications, and postoperative complications were collected over 12 months. The primary outcome measure was defined as an IOP within normal limits (<21 mm Hg) and at least a 20% reduction in IOP from baseline. Results: Mean IOP was significantly decreased in both groups after 1 year (p<0.001 from baseline). The success rate was significantly higher in the phaco-ECP group (69.6%) than in the phaco group (40%) after 1 year (p = 0.004). Reduction in mean IOP and number of medications was also greater in the phaco-ECP group after 1 year (IOP reduction: 4.5 ± 5.13 mm Hg vs 1.83 ± 3.61 mm Hg; p = 0.007; number of medications reduction: 0.73 ± 0.71 vs 0.23 ± 0.56; p = 0.001). Both groups achieved a similar improvement in VA. There was a higher incidence of minor and self-limiting complications in the phaco-ECP group (p<0.047). Conclusions: Phaco-ECP resulted in a greater reduction in IOP and number of medications than phacoemulsification alone in POAG.